Efektifitas Media Pop-Up Book terhadap Peningkatan Literasi Sains di Kelas IV pada Materi Tumbuhan - Yuliyana Yuliyana; Cucun Sunaengsih; Atep Sujana (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
Learning oriented towards scientific literacy has not been fully implemented well in learning. Training to fulfill these abilities can be trained since elementary school. The low ranking of scientific literacy in Indonesia in PISA data is a necessity to modify learning that is oriented towards scientific literacy, especially science learning. This research aims to determine the effectiveness of media in increasing the scientific literacy skills of students in elementary schools using pop-up book media. This research uses the Pre-Experiment Design (non-design) method with One-Group Pretest-Posttest Design. The research subjects consisted of 34 class IV students. Research data was obtained from expert validation on the media to be used and the effectiveness of the media using pretest and posttest written tests. The results of this research show that the pop-up book media obtained a material expert validation score of 88.09% in the very feasible category and a media expert validation score of 94.83% in the very feasible category. Then, the results of the pop-up book effectiveness test using pretest and posttest showed an N-Gain result of 0.6273 in the